Quantifying the Subjective Experience of Nasal Obstruction: A Review - Rossi Meyer, Monica K.; Most, Sam P. (Facial Plastic Surgery, 2023)
Nasal obstruction is an exceedingly common problem and challenging to treat due to its multifactorial etiology. Therefore, measuring treatment outcomes of nasal obstruction can be equally complex yet vital to appropriately assessing symptom improvement or resolution. Both physiologic and anatomic assessments of the nasal airway exist in addition to validated patient-reported outcome measures (PROMs), which objectify subjective nasal obstruction and sinonasal symptoms. Correlation between objective and subjective treatment outcome measures is controversial with clinical guidelines favoring the use of PROMs for surgical treatment of nasal obstruction. In this review, the anatomic and physiologic measurements of the nasal airway and validated PROMs will be discussed, as well as the rationale for implementing PROMs into the rhinoplasty surgeon's practice.
Keywords: patient-reported outcome measures; rhinoplasty; nasal obstruction